Careers in Ongoing Hierarchies - Demougin, Dominique; Siow, Aloysius (American Economic Review, 1994)
The probability that an unskilled worker can be successfully trained or screened to be a manager depends on the effort of the firm. With positive hiring costs, a firm prefers to train/screen its own managers. However, the optimal size of the firm for productive efficiency may conflict with efficient managerial husbandry. How a firm copes with the above constraint generates stochastic layoffs, lateral mobility, promotions, diverse earnings profiles, fast-track jobs, and up-or-out rules.